Strategy Selection for Natural Resource Conservation Capturing Vagueness through Integrated Neutrosophic CRITIC-MAIRCA Approach - Bahnishikha Roy Muhuri; Florentin Smarandache; M.K. Mondal; G.S. Mahapatra; B.S. Mahapatra (Neutrosophic Sets and Systems)
Conservation of natural resources like water, soil, and biodiversity is necessary for ecological balance and human survival. This article aims to identify potential ways to conserve natural resources while maintaining a balance between ecology and human survival. An integrated neutrosophic CRiteria Importance Through Intercriteria (CRITIC)-Multi-Atributive Ideal-Real Comparative Analysis (MAIRCA) approach is developed to handle uncertain and inconsistent information. The linguistic assessments of the criteria are quantified through single-valued neutrosophic sets (SVNSs). The CRITIC method evaluates the criteria weights to avoid subjective and biased assessments. The MAIRCA approach is improved in a neutrosophic context to identify the ranking of the alternatives. The combined neutrosophic CRITIC-MAIRCA approach determines the best way to preserve natural resources. The proposed method reveals that the most favourable ways to conserve natural resources are through research and monitoring, while the last option is sustainable practices. Comparison and sensitivity discussions of the proposed approach are conducted to check its consistency and robustness.